Employee Engagement: Generational Differences in the Workforce (Journal of Organizational Psychology, 2017)
One of the most important issues to emerge over the past 40 years has been the increasing diversity of the workforce. These differences can be attributed to age, gender, race, ethnicity, religion, socioeconomic background, education, experience, and other characteristics. Today, there are four different generations in the workforce—Baby Boomers, Generation X, Generation Y, and the Millennials. Generational differences contribute an additional complexity and challenge to management. One specific area of interest is the influence of one’s generation to the engagement of the employee. This study examines the differences in employee engagement across the three generations currently in the labor force—Baby Boomers, Generation X, and Millennials. Data were collected from published articles and a survey. The survey instrument was distributed through a centralized national company of smaller owned companies. A sample was drawn from a list of these companies. Statistical methods were applied to the results.
Keywords: Organizational Psychology; Workforce; Employee Engagement